Synthesis, characterization, and CO2 separation performance of polyether sulfone/EMIMTf2N ionic liquid-polymeric membranes (ILPMs) - Mannan, H.A. (Korean Society of Industrial Engineering Chemistry, 2017)
The objective of this research is to combine the superior features of polyethersulfone (PES) polymer and higher affinity of 1-ethyl-3-methyl imidazolium bis(trifluoromethylsulfonyl)imide (emimTf2N) ionic liquid for CO2 gas, in ionic liquid-polymeric membranes (ILPMs) at higher ionic liquid concentrations. The ionic liquid embedded membranes were characterized and tested for pure carbon dioxide and methane gases at 25 °C temperature and at a relatively higher pressure range of 5–25 bar. The morphology of the membranes was dense and defect free as deduced from FESEM analysis. The gas permeation studies confirmed that increasing IL content in ILPMs resulted in the enhancement of both CO2 permeability and CO2/CH4 selectivity simultaneously, due to high affinity of CO2 in IL. This was observed when the permeation of carbon dioxide increased significantly from 2.42 barrer for neat PES membrane to 298.84 barrer (124-fold increment) for ILPM containing 50 wt. % IL, at 25 °C and 25 bar. The resultant selectivity was improved from 15.91 to 57.53, which accounted for ∼3.6-fold increase in the ideal selectivity. The synthesized membranes are promising materials for industrial gas separation membranes for CO2 removal from CH4 gas at higher pressures and higher IL contents. © 2017 The Korean Society of Industrial and Engineering Chemistry